If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3m + -21) = 2(3m + 3) Reorder the terms: 3(-21 + 3m) = 2(3m + 3) (-21 * 3 + 3m * 3) = 2(3m + 3) (-63 + 9m) = 2(3m + 3) Reorder the terms: -63 + 9m = 2(3 + 3m) -63 + 9m = (3 * 2 + 3m * 2) -63 + 9m = (6 + 6m) Solving -63 + 9m = 6 + 6m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-6m' to each side of the equation. -63 + 9m + -6m = 6 + 6m + -6m Combine like terms: 9m + -6m = 3m -63 + 3m = 6 + 6m + -6m Combine like terms: 6m + -6m = 0 -63 + 3m = 6 + 0 -63 + 3m = 6 Add '63' to each side of the equation. -63 + 63 + 3m = 6 + 63 Combine like terms: -63 + 63 = 0 0 + 3m = 6 + 63 3m = 6 + 63 Combine like terms: 6 + 63 = 69 3m = 69 Divide each side by '3'. m = 23 Simplifying m = 23
| 2/5=7 | | 5x-(3x+3)=11 | | -17x-(10-x)=-58 | | p=2(2)+2(36) | | 5+8=3c | | 3(x-3)+16=4x+25 | | 40x-1=9 | | 4p+1.1=2600 | | 2.5x-1=9 | | 4p*1.1=2600 | | 2+5x=6+2x | | 14x+2=15x-5 | | 16-8y=4c | | 2(x+8)=22 | | 5y^2+11y+4=0 | | 12-6x=18+(-7) | | 9x^3+15= | | 8v^2-30v+18=0 | | sin(x)+x*cos(x)=0 | | 16x+10=122 | | 8b+11- 3b=2b+2 | | 3(1+2x)-4x=-(x+30) | | 3/4=-1 | | 5x^2-2x-7x=0 | | 5x-9=-16+6x | | 18+5x=13+-12x-1 | | 6s^2+59s+75=0 | | 4(2x+11)=92 | | 3x-11=33 | | 4(2x+3y)-3(x-y)= | | -18+5x=13+2x | | 65s^2+59s+75=0 |